PENGGUNAAN LKS UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR - Supriati Supriati (UNIB Press, 2020)
Thepurpose of this studyis to applythe use ofworksheets to increasestudent activityand achievement.ThisresearchhasbeencarriedoutbymeansofaschoolactionresearchinSD Negeri 9Lahat.Thisresearchwasconductedinthreecyclestofindoutthattheuseofstudentworksheets toimprovestudentachievementresultsfromthe firstcycletothethird cycle.Thisprovesthatthe applicationoftheuseofworksheetsnotonly increasesstudentlearningactivitiesbutalsoincreases understanding ofthematerialandthishastheeffectofincreasing studentlearning outcomes.PTS takingtechniquesbymeansofobservationandtests,whiletheexperimentalclassonlytestedthe use of worksheetsthattookclass5c.Data analysiswas carriedoutwithsignificantsignificance using thet-test.Basedontheanalysisofthisresearchdata,itwasfoundthattherearedifferencesin learning modelsthatuseLKStoimprovestudentlearningactivitiesandachievementinsocial studies learning.Thepurpose of this studyis to applythe use ofworksheets to increasestudent activityand achievement.ThisresearchhasbeencarriedoutbymeansofaschoolactionresearchinSD Negeri 9Lahat.Thisresearchwasconductedinthreecyclestofindoutthattheuseofstudentworksheets toimprovestudentachievementresultsfromthe firstcycletothethird cycle.Thisprovesthatthe applicationoftheuseofworksheetsnotonly increasesstudentlearningactivitiesbutalsoincreases understanding ofthematerialandthishastheeffectofincreasing studentlearning outcomes.PTS takingtechniquesbymeansofobservationandtests,whiletheexperimentalclassonlytestedthe use of worksheetsthattookclass5c.Data analysiswas carriedoutwithsignificantsignificance using thet-test.Basedontheanalysisofthisresearchdata,itwasfoundthattherearedifferencesin learning modelsthatuseLKStoimprovestudentlearningactivitiesandachievementinsocial studies learning.